Myocardial stress remodelling after regional infarction is independent of glycogen synthase kinase-3 inactivation - Webb, Ian G. (Academic Press, 2010)
Phosphorylation and inactivation of glycogen synthase kinase 3 (GSK-3) is observed in the failing heart induced by chronic pharmacological stress and aortic banding. Constitutive kinase activity attenuates pathological remodelling, suggesting an obligatory role in stress signalling. However, this has been challenged by recent data whereby conditional GSK-3β deletion has been shown to protect against post-infarct remodelling. Here, we set out to determine the chronic remodelling response to infarction in hearts of GSK-3α/β(Ala21/9) knockin (KI) mice encoding constitutively active GSK-3 isoforms. At 4 weeks after infarction there were significant increases in normalised heart weight and left ventricular (LV) muscle volume compared to sham in both KI and wild type animals. This was associated with an increase in LV cavity dimensions and remote LV wall thickness. Hypertrophy in both genotypes resulted in marked contractile impairment on both invasive and non-invasive interrogation. Increased phosphorylation of GSK-3β, but not GSK-3α, was demonstrated at 1 week after infarction and remained elevated at 4 weeks compared to sham-treated hearts. In conclusion, GSK-3β phosphorylation and inactivation occurs with, but is not an obligatory signalling event in, chronic post-infarct remodelling in the mouse heart. This highlights the heterogeneity of pathological hypertrophy and the divergent role of GSK-3 signalling in chronic myocardial stress.